New Flow Injection Method for Determination of Glutathione Using Merging Zone Technique - Muthana Salih Mashkoor (Journal of Global Pharma Technology, 2018)
New flow injection were designed for the determination of glutathione by Iodate and Iodide at λmax=350 nm with high efficiency and distinction, with new innovative design included tri-valve in one level. The best manifold and optimum conditions were managed at λ max=350nm. The calibration curve was fabricated   with linear range (1-80) ppm. The linearity (R2) value was 0.9990.The limit of detection value was 0.256 ppm. The limit of quantification value was 0.853 ppm. The dispersion coefficient value was 1.45 and 1.35 for the two concentrations 10 and 30 ppm respectively. Sampling rate was over the range 80sample per hour for every run cycle. The arrival time of sample/reagent zone from injection unit to flow cell was 20 seconds. Determination of GSH was applied on standard solutions, which gave high precision and accuracy with recovery in well worthily.Key words: Flow injection analysis, Glutathione, Iodate.